The Wild Duck’s Hedvig: An Adolescent Dragged to Suicide - Fahes, Safaa (European Scientific Journal, ESJ, 2023)
Adolescents predominantly experience fluctuations and turmoil during a stage that witnesses conflicts of multiple forms emanating from a wide variety of sources. Such individuals wallow in the mire of crises that start with quarrels within the family and self-harm, pass through drug abuse and end in suicide. It is the latter phenomenon that this paper seeks an investigation of, in particular as regards the suicide of Hedvig Ekdal in Henrik Ibsen’s play, The Wild Duck. Controversy looms large in the critical interpretations of Hedvig’s suicide, some construing it as an accidental fate, others accusing Gregers Werle, or blaming her father, Hjalmar, and still others seeing her mother, Gina, as the perpetrator. No matter who the culprit is, literature seems short of investigating the roots of this suicide from socio-psychological perspectives. This paper thus picks up the gap in existing literature so as to clarify why the sensitive adolescent girl, Hedvig, takes the matter of ending her life into her own hands.